Identification of novel risk loci and causal insights for sporadic Creutzfeldt-Jakob disease: a genome-wide association study. Issue 10 (October 2020) - Jones, Emma; Hummerich, Holger; Viré, Emmanuelle; Uphill, James; Dimitriadis, Athanasios; Speedy, Helen; Campbell, Tracy; Norsworthy, Penny; Quinn, Liam; Whitfield, Jerome; Linehan, Jacqueline; Jaunmuktane, Zane; et al.
Summary: Background: Human prion diseases are rare and usually rapidly fatal neurodegenerative disorders, the most common being sporadic Creutzfeldt-Jakob disease (sCJD). Variants in the PRNP gene that encodes prion protein are strong risk factors for sCJD but, although the condition has similar heritability to other neurodegenerative disorders, no other genetic risk loci have been confirmed. We aimed to discover new genetic risk factors for sCJD, and their causal mechanisms. Methods: We did a genome-wide association study of sCJD in European ancestry populations (patients diagnosed with probable or definite sCJD identified at national CJD referral centres) with a two-stage study design using genotyping arrays and exome sequencing. Conditional, transcriptional, and histological analyses of implicated genes and proteins in brain tissues, and tests of the effects of risk variants on clinical phenotypes, were done using deep longitudinal clinical cohort data. Control data from healthy individuals were obtained from publicly available datasets matched for country. Findings: Samples from 5208 cases were obtained between 1990 and 2014. We found 41 genome-wide significant single nucleotide polymorphisms (SNPs) and independently replicated findings at three loci associated with sCJD risk; within PRNP (rs1799990; additive model odds ratio [OR] 1·23 [95% CI 1·17–1·30], p=2·68 × 10 −15 ; heterozygous model p=1·01 × 10 −135 ), STX6 (rs3747957; OR 1·16 [1·10–1·22], p=9·74 × 10 −9 ), and GAL3ST1 (rs2267161; OR 1·18 [1·12–1·25], p=8·60 × 10 −10 ). Follow-up analyses showed that associations at PRNP and GAL3ST1 are likely to be caused by common variants that alter the protein sequence, whereas risk variants in STX6 are associated with increased expression of the major transcripts in disease-relevant brain regions. Interpretation: We present, to our knowledge, the first evidence of statistically robust genetic associations in sporadic human prion disease that implicate intracellular trafficking and sphingolipid metabolism as molecular causal mechanisms. Risk SNPs in STX6 are shared with progressive supranuclear palsy, a neurodegenerative disease associated with misfolding of protein tau, indicating that sCJD might share the same causal mechanisms as prion-like disorders. Funding: Medical Research Council and the UK National Institute of Health Research in part through the Biomedical Research Centre at University College London Hospitals National Health Service Foundation Trust.